2004
DOI: 10.2172/841309
|View full text |Cite
|
Sign up to set email alerts
|

Performance and degradation evaluation of five different commercial lithium-ion cells

Abstract: The initial performance of five different types of Li-ion rechargeable batteries, from Quallion Corp, UltraLife Battery and Toshiba, was measured and compared. Cell characterization included variable-rate constant-current cycling, various USDOE pulsetest protocols and full-spectrum electrochemical impedance spectroscopy. Changes in impedance and capacity were monitored during electrochemical cycling under various conditions, including constant-current cycling over 100% DOD at a range of temperature and pulse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…26 ) and NCA (e.g. 26,27 ). The dQ/dV vs. V curves do not change significantly as TMOBX is added and no extra peaks are observed that increase with TMOBX content, even when viewed on an expanded scale, suggesting no dramatic oxidation of TMOBX during the first charge of these materials.…”
Section: Resultsmentioning
confidence: 99%
“…26 ) and NCA (e.g. 26,27 ). The dQ/dV vs. V curves do not change significantly as TMOBX is added and no extra peaks are observed that increase with TMOBX content, even when viewed on an expanded scale, suggesting no dramatic oxidation of TMOBX during the first charge of these materials.…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the assumption of 3,000 battery cycles at an average charge swing of 34%, with a 24-kWh battery pack and 300 Wh/mi in plug-to-wheel vehicle efficiency. While the failure mechanisms of different types of lithium-based batteries are still being understood, it appears clear that for many of them, treatment of the battery in terms of ambient temperature and avoidance of long periods at high state-of-charge levels can have a larger effect on battery life than depth-of-discharge patterns (8,9). Longer and shorter battery-life expectancies are considered in the sensitivity analysis below; battery lifetimes may be shorter in warmer weather climates and longer in cooler climates because of the effect of warmer temperatures on increasing battery degradation and reducing battery lifetimes (10).…”
Section: Infrastructure and Subscription Estimatesmentioning
confidence: 99%